معوقات وعقبات الدعوية المعاصرة وطريقة علاجها في ضوء السيرة النبوية( دراسة وصفية): Contemporary Obstacles in Dawah and their Solutions in light of Seerah of Holy Prophet PBUH - Dr. Amjad Hayat; Dr. Noor Hayat Khan (MEI, 2023)
Praise be to Allah, the Lord of everything, and countless blessings be upon the most honorable of the prophets and messengers, our Holy Prophet PBUH and whoever follows his Sunnah. Dawah (Calling toward Allah) is the duty of prophets and messengers who are ambassadors of his Lord, the Most Exalted to the people, and the best of His servants. It is the job of the heirs of the prophets and is the best among all good deeds after faith. The consequences of Dawah appear in society in the form of correction of false beliefs, unity of Muslims, removal of various forms of polytheism, realization of truth, nullification of falsehood, enjoining good and forbidding the evil as well as jihad for the sake of Allah in order to remove the obstacles in the path of Allah Almighty. It is self evident that every virtuous cause face multiple obstacle which try to mitigate it. Similarly, the process of Dawah in contemporary age is facing various type of complications due to socio-political and economic advancement around the globe. These problems differ from one country to another, strength and weakness, as well as manifestations and methods of treatment. However, the most common obstacles include mockery of the da'i when calling to Allah Almighty, ignorance, illiteracy, deviant sects, accusations and stabbings, affliction and tribulations, sectarian fanaticism, jurisprudential disputes, Islamophobia, misleading media, economic problems, lack of suitable environment in which the da'wa grows, and the failure to provide a decent life for the contemporary da'i with respect to others. This research paper will undertake these obstacles and will provide the solutions in the light of Seerah of Holy Prophet PBUH